Problematika Diri Sebagai Rangsang Cipta Karya Seni Lukis Abstrak - Muhammad Hidayat; Suryanti Suryanti; Hamzah Hamzah (Institut Seni Indonesia Padang Panjang, 2022)
Problematics are obstacles or problems that must be solved; in other words, the problem is the gap between reality and something expected to work well to achieve maximum results. In everyday life, a person is never separated from various problems, one of which is the problems experienced while attending lectures. Problems arise from one's own negligence, resulting in self-defeating consequences. This is the basis for the creation of paintings. The form of the work presented is a two-dimensional work with an abstract style approach, emphasizing expressive and spontaneous lines using acrylic paint on canvas. The creation methods are preparation, observation, design, embodiment, and presentation. The creation of this painting has succeeded in producing five works entitled